Income variability, evolving diets, and demand for processed foods in Nigeria - de Brauw, Alan; Herskowitz, Sylvan (International Food Policy Research Institute, 2019)
We present evidence on evolving dietary patterns in Nigeria using three waves and six total rounds of household consumption data from the Nigerian Living Standards and Measurement Surveys between the years of 2011 and 2016. First, following conventional definitions in the literature, we show that Nigeria has not shown any aggregate increase in consumption of highly processed foods over this time period, contrary to studies elsewhere in the region. In fact, consumption of highly processed foods at home has decreased, while food away consumed away from home has risen substantially. We then show that estimates of food expenditure elasticities of different food types are highly sensitive to different estimation approaches, raising concerns regarding the existing evidence base on food consumption patterns reliant on estimation of food expenditure elasticities. Different specifications can lead to broadly differing conclusions about whether highly processed food is either the most or least elastic food category. In our preferred specifications, we find that elasticity of demand for food away from home is highest for the relatively wealthy and in the urban South. Within households, elasticities are highest in times of scarcity, suggesting that households cut food away from home when resources are relatively scarce.